The Social Capital Theory in the Light of a Centre-Periphery Comparison - Abamukong, Brendan Ngeloo; Jobst, Solvejg (International Dialogues on Education Journal, 2016)
The article examines the relationship between the social capital concept and school dropout rates from a global and multi-level perspective. Are there universal aspects of social capital that can predict dropout probability for at-risk young adults? If not, how do the correlations vary and to what extend can the differences be associated with variations in macro level state mechanisms in the context of the contemporary world’s social system? These questions are discussed empirically using a data set of 138 at-risk young adults in Cameroon and Germany. The results of the study show relatively higher correlations for Germany compared to Cameroon. The article concludes that context matters and aspects of macro-level state mechanisms and political institutions have important influences on the levels and patterns of micro- level social interactions in societies. This implies that areas with standardized macro-level democratic institutions will find it easier to develop generalized trust as well as to have higher levels of social capital formation. The need for the creation of a more equitable social and economic development policy which counteracts the inequality that is inherent in centre–peripheral relations is therefore highly recommended.